The impact of preservation techniques on bee pollen nutritional value, microbiological stability, and antioxidant properties - Lema, Filipe (2020)
After its collection the bee pollen can present moisture contents that can range from 18% to 25%. Thus, it is necessary to reduce the moisture content in order to maintain bee pollen overall nutritional quality and microbiological safety. Moreover, several studies have recently highlighted the beneficial biological properties of bee pollen, which may also be influenced by the preservation techniques applied to reduce the moisture content. Therefore, the main objective of this work is to provide an insight regarding the potential influence of preservation techniques on the nutritional value, microbiological quality, and antioxidant properties of bee pollen. The bee pollen, presented an initial moisture content of 13.8%, which was subsequently reduced to 9.6%, 9.8%, 10.1%, and 5.8% by oven-drying at 35ºC, 40ºC, and 45ºC, and freeze-drying, respectively. The nutritional value, microbiological quality, and antioxidant properties of the preserved bee pollen were assessed throughout time during a period of 6 months. In general, the different treatments showed no significant immediate impact on the nutritional value and microbiological loads of bee pollen, but some changes were observed on the antioxidant properties. Also, changes were observed after one month of storage, mostly in total viable counts and lactic acid bacteria.